O dêitico gestual como processo comunicativo no discurso interativo de sala de aula. - Oliveira, Cristiano Lessa de (2008)
This master work has the objective to discuss the deitic gesture, observing like the indicate, element which is considered a communicative act, at the moment of its discharges, in classroom, it can contribute to the construction of knowledge, as helping in the interactive process between classroom speech participants - teacher and students. In this discussion work, we understand that the act of pointing out doesn t work as an identificatory behavior, but also like something which permits the construction of sense. We developed an ethnographic study in the speech which happened in a public school in the city of Maceió - AL. The corpus was definided by Sciences video recordings classes from the sixth grade basically studies, orthographic transcriptions and captivation of pictures. Among the gesture categories, we chose as the observation focus the deitic gesture or the indicate (CAVALCANTE, 1994; MONDADA, 2005) because this gesture turned an important element, catching the speakers attention (students) turning the access of the discursive topic more accessiful, knowed, motivated, justified, legitimating its introduction. Our investigation has the theorical base the studies of the non-verbal and verbal elements, centered on the Conversation Analyses. In this sense, we followed the contributions of Kerbrat-Orecchioni (2006), Marcuschi (1997), Knapp & Hall (1999), and others. For these studies, we also used a literature which treats reference phenomena and deixis, taking the dates provided by Mondada (2005), Levinson (2007), and others. The results pointed diversity in the referential-gesture action, which allowed us to get the following classification: 1) conventional indicating; 2) pointing with the hand; 3) pointing for insistention gesture; 4) pointing with all the hand and fingers semi-manageable; and 5) pointing with objects among the fingers. The types of observed indicates contributed to the teacher to barter the texts sense done by her, especially when it was necessary to emphasize a particular term of the discursive topics. Pedagogically, the referential-gesture actions helped the speakers involvement, because they get possible the construction of knowledge developing an interactive habitat where was possible the students learning.